2007
DOI: 10.1007/s10658-006-9095-3
|View full text |Cite
|
Sign up to set email alerts
|

A new furovirus infecting barley in France closely related to the Japanese soil-borne wheat mosaic virus

Abstract: In April 2001, stunted barley plants bearing mosaic symptoms were observed in a field in France (Marne Department, 51). Rod-shaped and flexuous particles were visualized by electron microscopy and positive serological reactions were detected by ELISA with Barley yellow mosaic virus (BaYMV) and Soil-borne cereal mosaic virus (SBCMV) polyclonal antisera. The tubular virus which was soil transmissible to barley cv. Esterel was separated from BaYMV by serial mechanical inoculations to barley cv. Esterel. This furo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…This finding seemed more consistent with the fact that, in Europe, SBWMV had only been observed at Heddesheim in Germany (Koenig and Huth, ). However, SBWMV was recently reported in the Marne department of North East France (Hariri and Meyer, ) indicating that SBWMV may be more common in Europe than originally thought. It is possible that both SBCMV and SBWMV are present at René.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding seemed more consistent with the fact that, in Europe, SBWMV had only been observed at Heddesheim in Germany (Koenig and Huth, ). However, SBWMV was recently reported in the Marne department of North East France (Hariri and Meyer, ) indicating that SBWMV may be more common in Europe than originally thought. It is possible that both SBCMV and SBWMV are present at René.…”
Section: Resultsmentioning
confidence: 91%
“…However, recent sequence analysis of the genomes of these two viruses led to their designation as separate species as they only share 60–80% amino acid identity (Diao et al ., ; Koenig and Huth, ; Shirako et al ., ; Torrance and Koenig, ). The finding that wheat and barley grown in René soil were positive for SBCMV/SBWMV suggested that SBWMV was present at this location given known host ranges for these viruses; SBWMV infects both wheat and barley, but infection of barley by SBCMV has yet to be reported (Vallega et al ., ; Kastirr et al ., ; Hariri and Meyer, ; Lyons et al ., ). However, the genome sequence of a virus from the same location was shown to be SBCMV by Diao and colleagues ().…”
Section: Resultsmentioning
confidence: 99%
“…Soil-borne cereal mosaic virus (SBCMV), soil-borne wheat mosaic virus (SBWMV), and Chinese wheat mosaic virus (CWMV) are closely related furoviruses (Shirako et al 2000;Torrance and Koenig 2005;Hariri and Meyer 2007) that can infect durum wheat (Triticum turgidum L. var. durum), common wheat (T. aestivum L. var.…”
Section: Introductionmentioning
confidence: 99%
“…). SBCMV is a member of the genus Furovirus , in the family Virgaviridae (Hariri and Meyer , King et al. ).…”
mentioning
confidence: 99%